Communication of Career Women in Realizing a Harmonious and Loving Family in North Sinjai District, Sinjai Regency - Sutarni; Muliaty Amin; St. Nasriah (Jurnal Mercusuar, 2022)
This study employs a qualitative research approach conducted in the North Sinjai District, Sinjai Regency. The adopted approach is the Dakwah (preaching) and Communication approach. The primary data sources for this study are the informants, specifically women pursuing careers as teachers, midwives, lecturers, counselors, and office employees. Secondary data sources include books, the internet, ebooks, journals, and other complementary data. The data collection method involves several stages: observation, interviews, and documentation. Data analysis is conducted through three stages: data reduction, data presentation, and drawing conclusions. The research findings indicate that the communication methods employed by career women in realizing a harmonious and loving family (sakinah mawaddah warahmah) involve interpersonal communication, namely: 1. Openness, 2. Empathy, 3. Mutual support, 4. Positive attitude, 5. Equality. The implications of this research are as follows: 1. Career women in the North Sinjai District can balance their dual roles as wives and workers, thus fostering a family that embodies sakinah mawaddah warahmah by paying attention to the communication methods applied within the family. Healthy communication among family members is key to family harmony. 2. Husbands and families of career women can provide support for the chosen career path, as it is a crucial factor contributing to the success of building a family characterized by sakinah mawaddah warahmah.